Differential response to gepirone but not to chlordiazepoxide in malnourished rats subjected to learned helplessness - Camargo,L.M.M (2008)
The learned helplessness (LH) paradigm is characterized by learning deficits resulting from inescapable events. The aims of the present study were to determine if protein-calorie malnutrition (PCM) alters learning deficits induced by LH and if the neurochemical changes induced by malnutrition alter the reactivity to treatment with GABA-ergic and serotonergic drugs during LH. Well-nourished (W) and PCM Wistar rats (61 days old) were exposed or not to inescapable shocks (IS) and treated with gepirone (GEP, 0.0-7.5 mg/kg, intraperitoneally, N = 128) or chlordiazepoxide (0.0-7.5 mg/kg, intraperitoneally, N = 128) 72 h later, 30 min before the test session (30 trials of escape learning). The results showed that rats exposed to IS had higher escape latency than non-exposed rats (12.6 ± 2.2 vs 4.4 ± 0.8 s) and that malnutrition increased learning impairment produced by LH. GEP increased the escape latency of W animals exposed or non-exposed to IS, but did not affect the response of PCM animals, while chlordiazepoxide reduced the escape deficit of both W and PCM rats. The data suggest that PCM animals were more sensitive to the impairment produced by LH and that PCM led to neurochemical changes in the serotonergic system, resulting in hyporeactivity to the anxiogenic effects of GEP in the LH paradigm.